A numerical study on the optimization of ventilation mode during emergency of cable fire in utility tunnel. (June 2020) - Mi, Hongfu; Liu, Yaling; Jiao, Zeren; Wang, Wenhe; Wang, Qingsheng
Abstract: Recently utility tunnel fire safety is attracting more and more attention with the utility tunnel springing up in major cities of China. To cope with fires in utility tunnel, ventilation systems, fire-proof doors and sprinklers are usually installed. In order to obtain the optimized control modes for smoke propagation and better environmental conditions for inspection or maintenance personnel evacuation, it is necessary to study different combinational modes of ventilation systems, fire-proof doors, and sprinklers in case of fire. In this research, Fire Dynamics Simulator (FDS) was adopted to investigate the effectiveness of these modes during fires in utility tunnel. Temperature and visibility contours are depicted to compare the performance of three primary types of ventilation (natural system, extract system, and balanced system) with different switch modes of fire-proof door and sprinkler system. The results show that the optimization of smoke control modes in the utility tunnel depends significantly on the cooperation of the air supply system, air exhaust system, sprinkler system and the appropriate switch modes of fire-proof doors in different stages of fire development. As for the natural system, it is not recommended to adopt this system in fully developed stage of utility tunnel fire. As for the extract system and balanced system, it is better to close the fire-proof door and activate the sprinkler system. The results also demonstrate that with the appropriate switch modes of the fire-proof doors and sprinklers, smoke propagation in utility tunnel can be well controlled. These results could provide some valuable guidance for general smoke control design in utility tunnels.